MORPHOLOGICAL CREATIVITY IN BRAND NAMING: WORD FORMATION AND DERIVATIONAL PROCESSES - Riska Safitri Siregar; Siti Aisyah; Rifandy Wijaya; Dimas Bagoes Prasetyo; Dewi Nurmala (Fakultas Sastra UMN AL Washliyah, 2026)
This research investigates the strategic intersection of morphological theory and commercial branding by examining the linguistic mechanisms behind 50 global consumer brands. The primary objective is to analyze the derivational processes and creative word-formation strategies that facilitate brand distinctiveness. Utilizing a mixed-method approach supported by a corpus-based analysis, this study evaluates the structural patterns and functional impact of various linguistic innovations. Drawing on frameworks of derivational morphology and advertising management, the findings reveal that non-standard linguistic strategies are pivotal for establishing market resonance. Statistical data from the processed corpus indicate that compounding is the most dominant process (44%), followed by coining/acronyms (26%) and blending (24%), while standard derivation remains minimal at 6%. The analysis demonstrates that brands frequently employ